Canadian surgeon and resident involvement in international plastic surgery - Ying, Yvonne (Can J Surg, 2021)
Surgery has become increasingly recognized as an important component of health care in low and middle income countries (LMICs). Many surgeons from high income countries (HICs) are interested in working on improving access to surgery in LMICs. We sought to evaluate the involvement and potential barriers of Canadian plastic surgeons and plastic surgery residents in international work with an online survey. The survey indicated that plastic surgery residents have a high interest and involvement in international electives, with 45% of graduating residents previously involved. About 40% of respondents were involved in international projects, and academic plastic surgeons were more frequently involved than community surgeons. Taking time off work and personal/family commitments were cited as the greatest obstacles for those who are currently involved, whereas finding opportunities was the biggest challenge for those who would like to participate in the future.